1999
DOI: 10.4315/0362-028x-62.8.883
|View full text |Cite
|
Sign up to set email alerts
|

Alicyclobacillus in Orange Juice: Occurrence and Heat Resistance of Spores

Abstract: Spore suspensions of a pure culture of Alicyclobacillus acidoterrestris DSM 2498 were submitted to different heat treatments (60 degrees C for 60 min, 60 degrees C for 30 min, 70 degrees C for 20 min, 80 degrees C for 5 min, 80 degrees C for 10 min, 80 degrees C for 30 min, and boiling for 5 min) to determine the best activation conditions in orange juice. The best treatment for spore activation was shown to be 70 degrees C/20 min. Seventy-five samples of concentrated orange juice from 11 different suppliers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 0 publications
2
51
1
3
Order By: Relevance
“…0.05). D-values for conventional treatment obtained in this study (15.11 min for 80uC and 7.84 min for 90uC) were lower than the D-values previously reported for inactivation of A. acidoterrestris spores in orange juice with a similar pH range (4,5,14,26,27). The z-values for conventional treatment (17.89uC) also are higher than those previously reported (4,5,14,26,27).…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…0.05). D-values for conventional treatment obtained in this study (15.11 min for 80uC and 7.84 min for 90uC) were lower than the D-values previously reported for inactivation of A. acidoterrestris spores in orange juice with a similar pH range (4,5,14,26,27). The z-values for conventional treatment (17.89uC) also are higher than those previously reported (4,5,14,26,27).…”
Section: Resultscontrasting
confidence: 80%
“…Heat resistance studies have indicated that Alicyclobacillus spores can survive the usual hot-fill processes that are used with commercial juices (4,5,14,(24)(25)(26)(27). Data also indicate that increasing the uBrix makes the spores more resistant to heat.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse effects of dissolved oxygen on fruit juice quality have been investigated by many researchers and include degradation of ascorbic acid, increased browning and growth of aerobic bacteria and moulds (Eiroa, Junqueira, & Schmidt, 1999;Kennedy, Rivera, Lloyd, Warner, & Jumel, 1992;Meydev et al, 1977;Soares & Hotchkiss, 1999;Solomon, Svanberg, & Sahlstrom, 1995). Traditional methods for juice packaging aim to reduce the exposure of the juice to oxygen through the use of high barrier materials such glass or foil laminates in brickpacks, with or without nitrogen flushing (Zerdin et al, 2003) or improving gas barrier of PET by blending with aromatic polyamides (Hu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the spoilage of fruit juice by the thermoacidophilic spore-forming bacterium Alicyclobacillus acidoterrestris has been observed on a worldwide level [1,2]. Fresh orange juice and orange juice concentrate are often contaminated with spores of A. acidoterrestris, which have survived the pasteurization process [3,4].…”
Section: Introductionmentioning
confidence: 99%